The effect of mathematics teacher’s teaching method on form two students’ mathematics achievement / Aizad Amzari Mohd Radzuan, Nur Syazana Rosly and Noraini Ahmad - Mohd Radzuan, Aizad Amzari; Rosly, Nur Syazana; Ahmad, Noraini (Universiti Teknologi MARA, Perlis, 2023)
The teaching methods used by teachers will determine the extent of student’s performance in their academic. Teaching methods of mathematics include lecture, inductive, deductive, disclosure, problem solving and many more. Teacher may apply any strategies agreeing to unit of syllabus, accessible resource, and understudies in a course. When the teacher’s teaching method is not clear, the student feels that mathematics is a difficult subject in school. This will affect not only their liking of mathematics, but their diligence, intrigue, boredom, and self-efficacy beliefs related to mathematics. Students who think mathematics is a hard subject tend to have low interest in learning mathematics. They will feel that mathematics is a boring subject and will not push themselves to understand it. This study examines the effects of teaching method used by mathematics teachers on the achievements of Form 2 student. Quantitative research design was used to collect data, selection of sample was carried using simple random sampling whereas questionnaire was applied as the research instrument. The respondents comprised of 240 students and 150 were chosen as the sample. There were three main concerns involved in this study, which are to identify any relationships between the teachers’ studentcentered teaching method and the students’ interests in learning mathematics, the students’ perception towards mathematics subject and the significant differences between the mean score of teachercentered teaching method and student-centered teaching method for Form 2 students. The findings from this study revealed that teaching methods significantly affect student’s achievements. Additionally, student-centered teaching methods and teacher-centered teaching methods were still relevant to improve student’ academic performance.